Idiosyncratic Expression: Analysis of the Junior Students’ Paragraph Writing Test - Desfianur Ardhi; Ikhsanudin Ikhsanudin; Urai Salam (Jurnal Syntax Admiration, 2024)
The study analyzes the errors in the idiosyncratic expressions of 2nd-semester undergraduates in the English Language Education Program at Tanjungpura University. The objectives of the study are to describe the types of errors encountered in the students’ idiosyncratic expressions. The method of research is descriptive. The research participants were the 2nd-semester undergraduate students of the English Language Education Program of Tanjungpura University. The data were collected from corpora written by the students. Idiosyncrasy occurred in the students’ text. 187 constructions, out of 244, were deemed idiosyncratic. the types of errors found in the students’ idiosyncratic expressions were verb form errors (24,60%), subject and verb agreement errors (19,25%), plurality errors (9,63%), pronoun errors (9,09%), preposition errors (9,63%), verb tense errors (8,56%), word form errors (8,56%), article errors (5,88%) and word order errors (4,81%).